Commognitive and Learning Styles Study of Students' Middle School Understanding of Circles - Syahri, Andi Alim (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Understanding of mathematical concepts, especially in circle material, is influenced by students' learning styles and the way they communicate in solving problems. This study aims to analyze how students with visual, auditory, and kinesthetic learning styles apply the commognitive component in solving circle problems. The research method used is a qualitative approach with data collection techniques in the form of observation and interviews. The subject of this research is at public middle school 51 Makassar. The main instruments in this study include learning style questionnaires, written tests, and interviews. The data analysis technique includes three main stages: data reduction, data presentation, and conclusion drawing. To ensure data validity, this study used triangulation techniques and sources. The results indicated that students with a visual learning style used more visual mediators and words to understand the concept of a circle. Students with auditory learning styles tend to rely on narration in explaining concepts and are more fluent in oral communication, while students with kinesthetic learning styles use more routines and hands-on practice in solving problems. The conclusion of this study confirms that each learning style has a different tendency to utilize the commognitive component. Therefore, the optimal learning strategy should accommodate various learning styles so that students' understanding of mathematics concepts is more effective and meaningful.